The Result of the experimental trials of designing and testing of an electromagnetic device (MKTK-1, 2) to make castration of the young household animal (Mongolian Journal of Agricultural Sciences, 2020)
This article presents the result of research studies on developing, designing and testing a new special castrating method to increase the meat yield of adolescent animal /calves & lambs/ through proper exploration of physiological and biological capabilities of the young male animals. The core of our castrating method and technology lies in the fact that “cutting the vas deferens with no mechanical injury for livestock”. According to the field result which had been done in the countryside between 2012 and 2018, the average slaughter weight was 125.5kg, the slaughter yield was 53.9%, and the average cutability was 80.1% for 214 heads of 17-month old calves which were castrated by “castrated by thermal effect”. As an effect of application of this innovative method, the live weight increased by 37% and 42% for the experimental calves and lambs correspondingly. The slaughter yield of male calve was greater by 2.2% and the cutability was greater by 8.4-13.2% compare to a mature Mongolian cattle. Мал хөнгөлөх цахилгаан соронзон долгионы багаж (МХЦХ-1,2) зохион бүтээж, туршсан дүнӨсвөр эр мал /бяруу, хурга/-ын физиологи, биологийн нөөц, чадавхийг зохистой ашиглах замаар эдгээр малын махан ашиг, шимийг нэмэгдүүлэх зорилгоор мал хөнгөлөх өвөрмөц аргыг шинээр боловсруулж, үйлдвэрлэлд туршсан судалгааны үр дүнг энэхүү өгүүлэлд товч авч үзсэн болно. Бидний боловсруулсан мал хөнгөлөх арга, технологийн мөн чанар нь “малд механик гэмтэл үүсгэхгүйгээр үр дамжуулагчийг нь таслах”-д оршиж байгаа юм. Уг аргыг ашиглан 2012-2018 онуудад орон нутагт гүйцэтгэсэн хээрийн судалгааны дүнгээс үзэхэд  “төөнөж-таслах арга”-р хөнгөлсөн 214 толгой, 17 сартай бярууг нядлахад гулуузны дундаж жин 125,5 кг буюу нядалгааны гарц 53,9%, махны гарц 80,1% байв. Уг аргаар хөнгөлсөн бярууны амьдын жин 37%-иар, хурганы амьдын жин 42%-иар тус тус нэмэгдсэн байлаа. Эр бярууны нядалгааны гарц нь нас бие гүйцсэн Монгол үхрийн нядалгааны гарцаас 2,2%-иар махны гарц 8,4-13,2%-иар тус тус илүү байв.Түлхүүр үг: өсвөр эр мал, мал хөнгөлөх арга, мал хөнгөлөх цахилгаан хэрэгсэл (МХЦХ), малын махан ашиг шим